Analysis Students' Mastery on Identifying Adjective in Descriptive Text at XI Grade Students at SMAN 1 Kuok - Asilestari, Putri; Jannah, Isratul; haris, Hannisa (Journal of English Language and Education, 2026)
Classroom observations at SMAN 1 Kuok indicated that many eleventh-grade students have difficulty identifying adjectives in descriptive texts and often confuse them with other word classes, such as nouns and verbs. This challenge negatively affects their reading comprehension and descriptive writing skills. Based on this issue, the research question of this study is: How is the students’ mastery on identifying adjectives in descriptive text at XI grade students of SMAN 1 Kuok? The purpose of this study was to analyze students’ mastery on identifying adjectives in descriptive text at XI grade students at SMAN 1 Kuok. This research applied a qualitative descriptive approach, using a written test and an unstructured teacher interview as instruments. The test asked students to identify adjectives in a descriptive passage, classify their type, and explain their function. The teacher interview provided insight into students’ learning experiences, strategies used in teaching adjectives, and observed learning obstacles. The test results showed that only 3 out of 18 students (16.7%) reached the “Excellent” level, while 11 students (61.1%) were in the “Very Poor” category. Many students failed to differentiate adjectives from other parts of speech and lacked confidence in answering the test. From the teacher’s interview, it was revealed that although adjectives had been taught previously, students still showed low understanding in practical application. The teacher also noted that students were more familiar with adjectives in Bahasa Indonesia and recommended using contextual and visual learning strategies to support comprehension. This study highlights the need for improved vocabulary instruction, especially in the context of identifying adjectives within descriptive texts.